Chronic Pain Following Fracture-Related Surgery: Posttraumatic Rather Than Postsurgical Origin Promotes Chronification—A Prospective Observational Study With 1-Year Follow-up. (5th April 2022) - Aulenkamp, Jana L.; Malewicz, Nathalie M.; Brauckhoff, Julian D.; Zahn, Peter K.; Ebel, Melanie; Schnitzler, Romina; Clever, Julian; Geßmann, Jan; Bauer, Martin; Meyer-Frießem, Christine H.
Abstract : BACKGROUND: Chronic posttraumatic/postsurgical pain (CPSP) is common after traumatic or surgical damage. Exposure to both trauma and surgery, with the potential for repeated bone and nerve damage, may increase the risk of CPSP after fracture-related surgery. But the (long-term) incidences of CPSP and neuropathic CPSP and the ensuing burdens are unknown. Therefore, the patients were prospectively assessed within 1 year, and the patient-specific characteristics were explored. METHODS: Between 2017 and 2018, 127 patients (age: 52.9 ± 17.1 years, male: 55.1%) with traumatic fractures needing osteosynthesis (extremities: 91.3%) were assessed posttrauma (before surgery), postsurgery at days 1 to 5, 6 weeks, 3 and 12 months. The primary outcomes are as follows: incidence at 3 and 12 months of CPSP (defined as pain intensity on a numerical rating scale [NRS: 0–10] ≥3), secondary exploration: neuropathic CPSP (NRS ≥3 and Douleur Neuropathique 4 interview [DN4i] score ≥3 [Douleur Neuropathique interview: 0–7]); burden: quality of life (QoL, the EuroQOL five dimensions questionnaire [EQ-5D-3L] descriptive system); and inter alia, the number of analgesics (trial registration: DRKS00011601). RESULTS: The incidence of CPSP was 57.1% (52/91, n/N) at 3 and 42.7% (35/82) at 12 months postsurgery, including neuropathic CPSP 7.7% (4/52) and 17.1% (6/35), respectively. Descriptively, posttraumatic higher pain intensity at rest (difference of 0.9 ± 1.8 NRS) and the need for more frequent analgesics (by 34.3%) were associated with CPSP a year after surgery compared to those without. As soon as week 6, these patients had developed descriptively a 15% more impaired QoL, with 25% more impairment after 1 year. The patients with CPSP presented with at least 1 neuropathic symptom 12 months later in 68.6% (24/35) of cases, mainly with an early posttraumatic occurrence (without fulfilling the definition of neuropathic CPSP). CONCLUSIONS: After early fracture-related surgery, high incidences of CPSP (43%) were prospectively observed 1 year postsurgery, up to approximately 1 in 5 patients who had neuropathic CPSP. At the same time, CPSP was accompanied with an impacted QoL and analgesic dependence, both indicating clinical relevance. Moreover, the high incidence and the early posttraumatic occurrence of more intense pain suggest that the initial fracture-related trauma, rather than the surgical trauma, may predominantly trigger CPSP at Y1 (1 year). Therefore, these exploratory results set the direction of required future research. A future clinical hypothesis might be: treat first what hurts first. Abstract :